Nutrition assessment and its effect on various clinical variables among patients undergoing liver transplant - Bakshi, Neha; Singh, Kalyani (HepatoBiliary Surgery and Nutrition; Vol 5, No 4 (August 01, 2016): Hepatobiliary Surgery and Nutrition (Special Focus on Techniques and Innovations in Liver Surgery), 2016)
Background: Malnutrition is highly prevalent in patients undergoing liver transplantation and has been associated to various clinical variables and outcome of the surgery. Methods: We recruited 54 adult patients undergoing living donor liver transplant (LT) as study sample. Nutrition assessment was performed by body mass index (BMI), BMI for ascites, albumin, subjective global assessment (SGA) and anthropometry [mid upper arm circumference (MUAC), mid arm muscle circumference (MAMC), and triceps skin-fold (TSF)], Hand Grip strength, and phase angle of the body. Prevalence and comparison of malnutrition was performed with various clinical variables: aetiology, Child Turcotte Pugh scores and model for end stage liver disease (ESLD) grades, degree of ascites, blood product usage, blood loss during the surgery, mortality, days [intensive care unit (ICU), Ventilator and Hospital], and Bio-impedance analysis [weight, fat mass, fat free mass (FFM), muscle mass and body fat%]. Results: Assessment of nutrition status represents a major challenge because of complications like fluid retention, hypoalbuminemia and hypoproteinemia. Different nutrition assessment tools show great disparity in the level of malnutrition among ESLD patients. In the present study recipient nutrition status evaluation by different nutrition assessment tools used showed malnutrition ranging from 3.7% to 100%. BMI and anthropometric measurements showed lower prevalence of malnutrition than phase angle and SGA whereas hand grip strength showed 100% malnutrition. Agreement among nutrition assessment methods showed moderate agreement (κ=0.444) of SGA with phase angle of the body. Malnutrition by different assessment tools was significantly associated to various clinical variables except MELD and days (ICU, Ventilator and Hospital). SGA was significantly (P